Biodegradation of graphdiyne oxide in classically activated (M1) macrophages modulates cytokine production. Issue 30 (23rd July 2021) - Peng, Guotao; Duan, Tianbo; Guo, Mengyu; Xue, Yurui; Chen, Chunying; Li, Yuliang; Leifer, Klaus; Fadeel, Bengt
Abstract : Human macrophages are reprogrammed by graphdiyne oxide from M2 to M1 macrophages, leading to degradation of GDYO through a peroxynitrite-driven pathway with subsequent modulation of pro-inflammatory cytokines including IL-1β. Abstract : Graphdiyne oxide (GDYO) is a carbon-based nanomaterial possessing sp 2 and sp-hybridized carbon atoms with many promising applications. However, its biocompatibility and potential biodegradability remain poorly understood. Using human primary monocyte-derived macrophages as a model we show here that GDYO elicited little or no cytotoxicity toward classically activated (M1) and alternatively activated (M2) macrophages. Moreover, GDYO reprogrammed M2 macrophages towards M1 macrophages, as evidenced by the elevation of specific cell surface markers and cytokines and the induction of NOS2 expression. We could also show inducible nitric oxide synthase (iNOS)-dependent biodegradation of GDYO in M1 macrophages, and this was corroborated in an acellular system using the peroxynitrite donor, SIN-1. Furthermore, GDYO elicited the production of pro-inflammatory cytokines in a biodegradation-dependent manner. Our findings shed new light on the reciprocal interactions between GDYO and human macrophages. This is relevant for biomedical applications of GDYO such as the re-education of tumor-associated macrophages or TAMs.